Two-Carbon Ring-Enlargement of Cyclic 1,3-Diketones to Cyclic 1,5-Diketones - Kanaya, Shumpei; Asaji, Yuta; Yoshimura, Tomoyuki; Matsuo, Jun-ichi (Synlett, 2020)
3-Hydroxy-3-vinylcycloalkanones, which were prepared from the corresponding cyclic 1,3-diketones by mono-vinylation, were rearranged to two-carbon ring enlarged cyclic 1,5-diketones by treatment with a catalytic amount of potassium tert-butoxide.
Keywords: ring enlargement; cyclic 1,3-diketone; cyclic 1,5-diketone; mono-vinylation; potassium tert-butoxide